Evaluation of Combined Dilute Acid-Kraft and Steam Explosion-Kraft Processes as Pretreatment for Enzymatic Hydrolysis of Pinus radiata Wood Chips - Pablo Reyes; Nicole Márquez; Eduardo Troncoso; Carolina Parra; Regis Teixeira Mendonça; Jaime Rodríguez (BioResources, 2015)
The combination of hemicellulose pre-hydrolysis by dilute acid or steam-explosion followed by kraft pulping was one approach evaluated in this work to generate pulps from radiata pine wood chips amenable to saccharification by enzymatic hydrolysis. Dilute acid (combined severity factor, CS = 1.67) and steam explosion (severity factor, log Ro = 4.09) treatments were able to solubilize approximately 53% and 63% of the original hemicelluloses content in wood, respectively. Extracted wood chips were subjected to kraft cooking (170 °C, 16-18% active alkali, 30% sulfidity and 1200 H-factor) to produce pulps that were further saccharified by cellulases. Lignin removal increased with increasing active alkali, affording delignification levels 28% for dilute acid and 68% for steam explosion extraction pretreatment pulps. Enzymatic digestibility of P. radiata pulps were low, and only samples pretreated by steam explosion reached glucan-to-glucose conversion near to 75%; this treatment was 31% and 37% higher than that obtained with wood chips that were pretreated by dilute acid extraction.